When Ghosts Can Talk: Informant Reality and Ethnographic Policy - James M Nyce; Sanna Talja; Sidney Dekker (Journal of Ethnology and Folkloristics)
This paper argues that researchers doing ethnography can fail in their commitment to take what their informants say seriously. This often occurs, despite ethnographers’ best intentions, when informant statements depart radically from Western distinctions between what is real and what is imaginary. When informants talk about things like ghosts, witches and magic, there is a tendency to apply analytic strategies which translate these informant statements about the world so they conform to Western understandings about what is possible in the world and what is not. This article describes for example some commonly applied interpretive moves used in dealing with informant statements about other-than-human persons. The analytic models and categories we use in these cases are equivalent to often tacit and taken-for-granted Western strategies for dealing with ‘non-existent things’ and these make it impossible to take native statements at face value. We could turn the situation around in ethnographic analyses if we put under the microscope our own Western taken-for-granted assumptions and did so by taking definitions of reality, community, and the person radically different from our own seriously.